Assessment of Personality Functioning in Adolescence: Development of the Adolescent Personality Structure Questionnaire. (June 2022) - Benzi, Ilaria M. A.; Fontana, Andrea; Di Pierro, Rossella; Perugini, Marco; Cipresso, Pietro; Madeddu, Fabio; Clarkin, John F.; Preti, Emanuele
Adolescence is a crucial period for the development of personality and its dysfunctions. In this regard, it is essential to evaluate the nature and degree of maladaptive personality functioning. However, measures currently available present some limitations, mainly being adaptations from adult's tailored instruments and length. Moreover, no instrument considers the crucial dimensions related to body development and sexuality. This contribution presents data on the Adolescent Personality Structure Questionnaire (APS-Q) development, a self-report measure to capture core aspects of personality functioning in adolescence while being agile and reliable. On two large samples of adolescents (total N = 1, 664), we investigated the psychometric properties of the APS-Q. We explored its factor structure and construct and incremental validity in the first sample, testing specific associations with existing measures of severity of personality pathology, maladaptive personality traits, and psychological distress. In the second sample, we confirmed its factor structure, assessing gender and age invariance. Overall, our findings support the APS-Q's validity as a reliable and useful measure to assess personality functioning. Moreover, the APS-Q highlighted developmentally vital dimensions such as self-functioning (encompassing mental and bodily changes and considering the dimension of sexuality), interpersonal functioning (discriminating the dimensions of family and peers), and emotion regulation.